EVALUASI KINERJA DRAINASE JALAN SOEKARNO-HATTA KOTA BINJAI - Rahmadani, Sarra; Sutrisno, Sutrisno; Harahap, Rumilla; Wibowo, Harry; Zulfikar, Ahmad; Fadillia, Mena; Barlian, Edo; Indrayani, Indrayani (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2024)
Jalan Soekarno-Hatta is located in East Binjai District, Binjai City. Along this road, there is always quite high flooding when it rains. Flood events are usually caused by the intensity of rainfall and less than optimal drainage performance, where drainage should be a system whose function is to channel and circulate air that comes from rain, or seepage experiences damage and sedimentation so that it cannot function optimally. In order to minimize flooding on Jalan Soekarno-Hatta, it is necessary to evaluate drainage performance by reviewing existing conditions, taking into account rainfall intensity values and planned discharge to determine optimal capacity for more optimal drainage performance in collecting, channeling and channeling rainwater. This was done using an evaluative descriptive method with the length, width and depth of the drainage observed at 1630 m, 110 m and 1.27 m. The results were that the selected rainfall intensity value (period 5; year, 2027) was 125.866 mm/hour, concentration time (tc) 184.67 hours, drainage coefficient 0.925 resulting in planned discharge>drainage discharge (Qr>Qs) namely 278102.6 m3/ sec > 31478.6 m3/sec. These results indicate that Soekarno-Hatta's drainage capacity is unable to accommodate large (planned) discharges, resulting in flooding. Solutions that can be applied are reducing sedimentation, increasing the dimensions of the drainage itself or forming biopores.